Children Exposed to Intimate Partner Violence During Confinement: Characteristics by Age and Sex - Alcántara-López, Mavi; Castro, Maravillas; Martínez-Pérez, Antonia; Fernández, Visitación; Negrón-Medina, Kaveri; López-Soler, Concepción (Frontiers in Psychology, 2022)
The COVID-19 pandemic and restrictions imposed to stop its advance have affected the entire population. Children with difficulties or in vulnerability situations prior to the pandemic might have suffered an even greater impact. This present study examines the psychological impact of quarantine on children and adolescents exposed to intimate partner violence against their mothers. Participants were 185 mothers who reported 269 children, as well as 108 children who self-reported. An emotional and behavioral checklist was administered to both mothers and children throughout confinement. Results show mothers observed changes in their children´s psychological state. Children, in turn, reported an increase in different variables. Mothers reported a higher percentage of general increase for both general and severe symptoms than their children. Differences were found by sex, age, and attendance or not to psychological treatment by the children. Future research with similar population groups is necessary to establish the support and intervention children require in similar contexts, as well as to clarify possible causes of differences found by age and sex.